« Rejoindre les civilisations », Victor Brauner et sa collection d’arts extra-européens - Noémie Fillon (Les Cahiers de l'École du Louvre)
Put together mostly between the mid-1950s and the early 1960s, the collection of the artist Victor Brauner (1903–1966) is mainly made up of works from West Africa and Papua New Guinea. Now in the Musée d’Art Moderne et Contemporain de Saint-Étienne Métropole, the collection has been studied little as has the artist’s relationship to it. This article aims to shed light on Brauner’s putting together of the collection. The artist frequented the second generation of Parisian markets that emerged after the Second World War and also acquired works in Amsterdam. There will also be an analysis of the various ways, both distinct and complementary, he regarded the works collected –formally, intellectually, “magically” and “fraternally” – to give an account of the plural nature of his relationship to extra-European art and of the dialogue between it and his own work.